Performance e registro: a produção performática de Claudia Paim - Neves, Daniele Quiroga (2013)
Grounded on a research based theoretical, historical and critical, the present speech focuses on a study about technical, aesthetic and conceptual possibilities of the live performances image-document. While technical images based on photographic and videographic apparatus, the documents are understood like possible alternatives to knowledge of the performance art, yet have being fragmentarily portrayed and essentially changed by media. As a study object, the images of the production of the porto-alegrense artist Claudia Paim are analyzed.